Editorial to the Special Issue - Philip Arestis (Intervention. European Journal of Economics and Economic Policies, 2011)
This special issue of Intervention. European Journal of Economics and Economic Policies is devoted to Geoff Harcourt, self-proclaimed Australian patriot and Cambridge economist. His work is squarely within the Political Economy approach to economics. In 2010 Geoff Harcourt decided to return back to his Australian roots and it is for this reason that the organisers of the 7th international conference, Developments in Economic Theory and Policy, Bilbao (Spain), 1–2 July 2010, Department of Applied Economics V, University of the Basque Country, and Cambridge Centre for Economic and Public Policy, University of Cambridge, set up two sessions to celebrate Geoff Harcourt's work. The editors of Intervention very kindly offered to publish the proceedings of the two sessions in this issue. Not only did Geoff Harcourt attend the conference, he also contributed to the sessions. This special issue begins with his contribution.
Keywords: 330